(untitled) (Fiep Bulletin - online, 2015)
In swimming the corporal weight represents only 10% of the weight in land, however the studies are many that relate the percentage of corporal fat with the performance of swimming, therefore the fluctuation is intimacy on to the components of the corporal composition, a small percentage of fat is necessary for the swimmer, but it is observed that fat swimmers do not obtain to dislocate themselves with much rapidity, however the biomechanics explains this situation, therefore for the each armful applied force it is the value of its proper weight. The evaluation of the broken up corporal composition in four components is very important so that the technician, it gets predictions, as much related to the levels of health and quality of life, as well as with the performance in swimming. The objective of the present study of descriptive characteristic, experimental with typology of profile it was to analyze and to diagnosis through the anthropometric method of cutaneous folds and protocol calculations of Jackson and Pollock the corporal composition of swimmers of the category to master. The sample was composed for 21 swimmers with age between 26 and 61 years (men n=15 and women n=6) members of the Acquamaster of Foz do Iguassu - Pr. The average values and found shunting line standard for swimmers of the masculine and feminine sex how much its percentage of corporal fat had been of 18,32 +/- 5,60 and 31,35 +/- 9,27, respectively. It is observed then, the necessity of an orientation to the training level relating the nutrition, also characterizing the variable difference of the sample, characteristic of the amateur sport.